2007
DOI: 10.1002/cncr.22396
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated or conformal radiotherapy improves the quality of life of patients with nasopharyngeal carcinoma

Abstract: BACKGROUND.It was reported previously that the dosimetric superiority of conformal radiotherapy (RT), either 3‐dimensional conformal RT (3D‐CRT) or intensity‐modulated RT (IMRT), over conventional 2D‐RT translated into clinical benefits for patients with nasopharyngeal carcinoma (NPC). In this study, the authors compared quality‐of‐life (QOL) outcomes of NPC survivors who received treatment with 1 of 4 different RT techniques at a single institute during different periods.METHODS.The authors analyzed QOL data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 37 publications
3
61
1
1
Order By: Relevance
“…Several strategies, such as systemic amifostine, [22][23][24][25] IMRT, [26][27][28][29] pilocarpine, [30][31][32][33][34][35][36] and the salivary gland transfer procedure reported by Seikaly and Jha and their respective colleagues, 8,9,13 have been tried over the years in attempts to reduce xerostomia. IMRT strategies have focused primarily on saving 1 or both of the parotid glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies, such as systemic amifostine, [22][23][24][25] IMRT, [26][27][28][29] pilocarpine, [30][31][32][33][34][35][36] and the salivary gland transfer procedure reported by Seikaly and Jha and their respective colleagues, 8,9,13 have been tried over the years in attempts to reduce xerostomia. IMRT strategies have focused primarily on saving 1 or both of the parotid glands.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT strategies have focused primarily on saving 1 or both of the parotid glands. [26][27][28][29] Investigators are now, however, focusing their attention on the importance of submandibular salivary gland salivary contributions. The use of amifostine has decreased the incidence of xerostomia during radiotherapy in patients with head and neck cancer in a few randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Investigators are now, however, focusing their attention on the importance of submandibular salivary gland salivary contributions. Eisbruch et al are investigating the possibility of sparing both the parotid and the submandibular salivary gland by the combined use of intensity-modulated radiation therapy (for parotids) and Amifostine for the cytoprotection of the submandibular salivary gland.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Xerostomia impairs mastication, deglutition, gustation, and causes nutritional compromise, sleep disruptions, and change in oral microbial flora leading to caries. 4,5 Several strategies such as systemic Amifostine, [6][7][8][9] intensity-modulated radiation treatment (IMRT), [10][11][12][13] pilocarpine (Salagen, Pfizer Canada, Mississauga, Ontario), [14][15][16][17][18][19][20] acupuncture, 12 and Seikaly-Jha salivary gland transfer (SGT) procedure [22][23][24] have been tried over the years in an attempt to reduce xerostomia.…”
mentioning
confidence: 99%
“…Compared with conventional 2D techniques and 3D crt, imrt can provide superior dose coverage to the tumour and better sparing of surrounding tissues, potentially improving local control and long-term survival and, more importantly, enhancing qol for these patients 40,41 . Hisung et al 42 reported that, compared with 5-field 3D crt, 5-to 7-field imrt distinctly reduced radiation in the brain stem by about 16%.…”
Section: Is Imrt a Superior Technique Compared With Other Radiotherapmentioning
confidence: 99%